Systematic review, methodological appraisal, and recommendation mapping of clinical practice guidelines for managing patients with Stevens-Johnson syndrome and toxic epidermal necrolysis - Mohammed AlFada; Hend Alotaibi; Sahar Alsharif; Ahmad Hecham Alani; Andrea Andrade-Miranda; Camila Montesinos Guevara; Yaolong Chen; Ruobing Lei; Jorge Acosta-Reyes; Pamela Velásquez-Salazar; Ahmed El-Malky; Yasser S. Amer (Journal of Dermatological Treatment)
Purpose The Appraisal of Guidelines for Research and Evaluation II Instrument (AGREE II) was developed to enhance the methodological rigor of clinical practice guidelines (CPGs), aiming to generate trustworthy recommendations for various clinical scenarios. Despite its importance, there exists a gap in the quality of CPGs pertaining to Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis (SJS-TEN). The aim of the study was to evaluate SJS-TEN CPGs to shed light on areas for enhancing SJS-TEN guidelines’ quality.Materials and methods A systematic review was conducted to identify SJS-TEN CPGs from January 2011 to December 2023 across bibliographic and guideline databases, as well as dermatology association websites. Four reviewers employed the AGREE II instrument to appraise the quality of eligible CPGs. Subsequently, AGREE II domain scores were calculated and their recommendations mapped.Results and Conclusions Seven eligible SJS-TEN CPGs reviewed, originating from Europe, North America, Asia, and an authorship Group. The highest AGREE II domain scores were observed in scope and purpose (mean: 63%, standard deviation [SD]: 23.195%) and clarity of presentation (mean: 70%, SD: 14.5%). Conversely, the lowest score was noted in the applicability domain (mean: 28%, SD: 17.44%). Only two guidelines by the British Association of Dermatologists (28.6%) met the ‘recommend’ level. Recommendations from all CPGs were compared in tabular form.